2019
DOI: 10.3390/cancers11070915
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Immune Microenvironment in Lymphomas of B-Cell Origin: From Biology to Clinical Application

Abstract: In lymphomas of B-cell origin, cancer cells orchestrate an inflammatory microenvironment of immune and stromal cells that sustain the tumor cell survival and growth, known as a tumor microenvironment (TME). The features of the TME differ between the different lymphoma types, ranging from extremely inflammatory, such as in Hodgkin lymphoma, to anergic, leading to immune deficiency and susceptibility to infections, such as in chronic lymphocytic leukemia. Understanding the characteristic features of the TME as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 233 publications
(279 reference statements)
0
24
0
Order By: Relevance
“…50, 51 52 Although PD-L1 expression has been largely investigated in B cell lymphomas, the distinction of its expression in cellular microenviroment and/or in tumour cells has not been made in most studies. [1][2][3][4] Here we showed that EBV in BL might induce PD-L1 expression on tumor cells in a minority of cases characterized by a non-canonical latency with LMP2A positivity. On the other hand, it might influence PD-L1 upregulation on TAMs also in cases with canonical EBV latency I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50, 51 52 Although PD-L1 expression has been largely investigated in B cell lymphomas, the distinction of its expression in cellular microenviroment and/or in tumour cells has not been made in most studies. [1][2][3][4] Here we showed that EBV in BL might induce PD-L1 expression on tumor cells in a minority of cases characterized by a non-canonical latency with LMP2A positivity. On the other hand, it might influence PD-L1 upregulation on TAMs also in cases with canonical EBV latency I.…”
Section: Discussionmentioning
confidence: 99%
“…Over recent years, the understanding of the biology of B-cell lymphomas has advanced significantly with the identification of the role played by the tumour microenvironment (TME) in lymphomagenesis. 1,2 The TME of B-cell lymphomas mainly contains variable numbers of mesenchymal stem cells, immune cells and soluble factors. The complex interplay between tumour cells and TME regulates tumorigenesis and provides novel targets for immunotherapies.…”
Section: Introductionmentioning
confidence: 99%
“…Although PD-L1 expression has been largely investigated in B cell lymphomas, its expression in cellular microenviroment and in tumour cells has not been well defined in most studies [1][2][3][4] .…”
Section: Pd-1 Detection In Activated T-cells Might Represent a Reactimentioning
confidence: 99%
“…Over recent years, the understanding of the biology of B-cell lymphoma has advanced significantly with the identification of the role played by the tumour microenvironment (TME) in lymphomagenesis 1,2 . The TME of B-cell lymphomas mainly contains variable numbers of mesenchymal stem cells, immune cells and soluble factors.…”
Section: Introductionmentioning
confidence: 99%
“…The TME of CHL is composed of mainly inflammatory immune cells and only a small percentage of the cells, approximately 1% are malignant Hodgkin Reed-Sternberg (HRS) cells [41]. Thus, the role played by macrophages is especially important in the pathogenesis of CHL.…”
Section: Classic Hodgkin's Lymphomamentioning
confidence: 99%